Technologies in Distance Education: Challenges and perspectives in the brazilian educational system (Research, Society and Development, 2024)
This research aims to reflect on the new technologies applied in the Brazilian educational system and the use of VLE in distance learning. Methodology, this is a narrative bibliographic review of a qualitative nature. This investigation presented concepts of distance education and the possibilities, challenges, and perspectives of using educational technologies in distance learning. Distance education is training in which teaching-learning activities occur regardless of students and teachers being together in the same place or time. Several concepts define EAD and mention the technologies used to assist the education process. We can define distance education as a form of education in which learning is carried out at a distance, physical and temporal, mediated by a technology tool responsible for allowing communication and interaction between participants. Research shows that technology enables communication between students and teachers, as they are not together in a room like in conventional education. Most of the courses offered at a distance, despite using advanced and modern technologies, continue to be based on outdated pedagogical practices, focusing on informative and instructive aspects, when they should address the constructive, creative, and reflective ways related to the process of learning and issues involving the development of knowledge.